Factors influencing the synthesis and the post-modification of PEGylated pentafluorophenyl acrylate containing copolymers - Beija, M.; Li, Y.; Lowe, Andrew; Davis, T.; Boyer, C. (2013)
Copolymerization reactions involving oligoethylene glycol acrylate (OEGA) or diethylene glycol acrylate (DEGA) with pentafluorophenyl acrylate (PFPA) have been performed by reversible addition fragmentation transfer (RAFT) polymerization. The effect of the reaction conditions on the nucleophilic acyl substitution reactions of PFPA was studied using a model amine (furfuryl amine). The resulting PEG/PFP functional copolymers were then used as scaffolds to produce a library of polymers by reaction with a range of amines.